The effects of sex and load on quantifying the bilateral force deficit during an upper body Wingate test - Angie K. Antolinez; Philip F. Edwards; Michael W. R. Holmes; Duane C. Button; Duane C. Button (Frontiers in Sports and Active Living)
IntroductionThe bilateral deficit (BLD) is a reduction in the amount of force during a bilateral task vs. the total force from the unilateral limbs performing the same task. We quantified the BLD during an upper body Wingate Anaerobic Test (WAnT) and evaluated the influence of sex and load on the BLD in force.MethodsEighteen participants performed maximum handgrip strength, voluntary isometric contractions (MVIC), and three 30s WAnTs. In each session they completed the tasks with the dominant-arm, non-dominant arm and with both arms, randomly. WAnT intensities were 3, 4, and 5% body weight (BW). Instantaneous force data was used to calculate the BLD.ResultsMales showed greater (p < .001) BLD of force at 3, 4, and 5% BW than females by −17, −27.6 and −36%, respectively and had a greater (p < .001) BLD of force than females throughout time points 1–10 s, 11–20 s, and 21–30 s by −16, −29 and −35%, respectively. Females showed a difference (p < .001) in BLD of force between loads (−19% at 3%, −10% at 4% and +7% at 5%). Males had an increase (p < .001) in BLD of force from the beginning to the end of the WAnT starting with −18% (1–10 s), −38% (11–20 s) and −40% (21–30 s). WAnT had the highest BLD, followed by MVIC and grip strength.DiscussionBLD in force is present during WAnTs and the sex-load interaction is important for determining this BLD during this maximal cycling test. Thus, when developing training or rehabilitation programs related to BLD in force, sex, load and exercise type should be taken into consideration.